COMPARATIVE PERFORMANCE OF PARENTS AND THEIR FOUNDATION CROSSES OF BIVOLTINE SILKWORM, BOMBYX MORIL. WITH REFERENCE TO EGG YELD PARAMETERS - PALLAVI, S.N.; BASAVARAJA, H.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
In the present investigation, 10 bivoltine breeds maintained at Central Sericultural Research and Training Institute, Mysore, and their 12 foundation crosses were used to evaluate the reproductive parameters. Important productive traits viz., the number of eggs per laying, egg recovery percentage, egg yield per kilogram of Seed cocoons, number of eggs per gram, percentages of pupal mortality, non diapausing eggs and unfertilized eggs were studied and the improvement in the Chinese and the Japanese type foundation crosses was estimated. Statistical analysis of the data, revealed significant differences (p<0.05) between the parents and their foundation crosses for all the parameters considered for the study. Heterosis expressed for eggs per laying, egg recovery and the egg yield in the foundation crosses was 16.8. 21.2 and 23.9% respectively, over their parental breeds. There was significant reduction (p<0.05) in the percentages of dead pupae, non diapausing eggs and of unfertilized eggs. The overall results are imperative that the foundation crosses are superior in terms of quality of seed cocoons and increased egg yield, which would reflect in further combinations of these crosses to form the double hybrids. Utilization of foundation crosses hence, can be an effective means in reducing the cost of egg production, which gains importance from the point of view of the industry.